2013
DOI: 10.1126/scisignal.2004111
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine Transfer Protein Interacts with Thioesterase Superfamily Member 2 to Attenuate Insulin Signaling

Abstract: Phosphatidylcholine transfer protein (PC-TP) is a phospholipid-binding protein that is enriched in liver and that interacts with thioesterase superfamily member 2 (THEM2). Mice lacking either protein exhibit improved hepatic glucose homeostasis and are resistant to diet-induced diabetes. Insulin receptor substrate 2 (IRS2) and mammalian target of rapamycin complex 1 (mTORC1) are key effectors of insulin signaling, which is attenuated in diabetes. We found that PC-TP inhibited IRS2, as evidenced by insulin-inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 44 publications
(96 reference statements)
0
47
0
Order By: Relevance
“…However, knockdown of Them2 or PC-TP expression did not impair IP 3 -mediated ER calcium release ( Figure 3L). We previously demonstrated that knockdown of Them2 or PC-TP expression in HEK 293E cells activates Akt and the mammalian target of rapamycin (mTOR) (16). We found that the regulation of calcium fluxes by Them2 and PC-TP occurs independently of Akt and mTOR activity, since inhibiting Akt or mTOR activity with GDC-0941 or rapamycin, respectively, did not abolish the effects of Them2 and PC-TP on ER calcium fluxes (Supplemental Figure 7).…”
Section: Them2mentioning
confidence: 99%
See 4 more Smart Citations
“…However, knockdown of Them2 or PC-TP expression did not impair IP 3 -mediated ER calcium release ( Figure 3L). We previously demonstrated that knockdown of Them2 or PC-TP expression in HEK 293E cells activates Akt and the mammalian target of rapamycin (mTOR) (16). We found that the regulation of calcium fluxes by Them2 and PC-TP occurs independently of Akt and mTOR activity, since inhibiting Akt or mTOR activity with GDC-0941 or rapamycin, respectively, did not abolish the effects of Them2 and PC-TP on ER calcium fluxes (Supplemental Figure 7).…”
Section: Them2mentioning
confidence: 99%
“…To validate the importance of Them2-PC-TP interactions in regulating the ER stress response, we treated mice with the PC-TP inhibitor compound A1 (16,17,19,23). In Them2 +/+ mice, inhibition of PC-TP by compound A1 before tunicamycin administration led to increased PERK activity and reduced activities of IRE1α and eIF2α relative to vehicle-treated controls (Supplemental Figure 4).…”
Section: Critical Contributions Of Them2 and Pc-tp To Er Stress In LImentioning
confidence: 99%
See 3 more Smart Citations